Oxide-like enzyme Fe3O4 (at) MnO2 nano material as well as preparation method and application thereof

Fe3O4@MnO2 nanomaterial prepared by solvent-thermal method and potassium permanganate oxidation method is used for double-anti-anti-sandwich detection of rotavirus, solving the problems of insufficient sensitivity and complex operation of existing detection methods, and achieving high sensitivity and simplicity detection effect.

CN119215927APending Publication Date: 2024-12-31ACADEMY OF MILITARY MEDICAL SCIENCES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411390851.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing rotavirus detection methods have insufficient sensitivity, complex operation, expensive equipment or require professional technology, making it difficult to effectively conduct testing in general hospitals.

Method used

The oxidase-like active Fe3O4@MnO2 nanomaterial was prepared by solvothermal method and potassium permanganate oxidation method, which was used to establish a human rotavirus double-anti-sandwich detection method, which improved detection sensitivity and simplified operation.

Benefits of technology

High sensitivity detection for rotavirus is achieved, with a detection sensitivity of 3.799copies/μL, simplifying detection operations and reducing equipment and technical requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215927A_ABST
    Figure CN119215927A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nano materials, and provides an oxide-like enzyme Fe3O4 (at) MnO2 nano material as well as a preparation method and application thereof. According to the invention, a solvothermal method and a potassium permanganate oxidation method are utilized to prepare the oxide-like enzyme activity Fe3O4 (at) MnO2 nano material, and the oxide-like enzyme activity Fe3O4 (at) MnO2 nano material comprises Fe3O4 nano particles and manganese dioxide; the manganese dioxide is generated in situ on the surfaces of the Fe3O4 nanoparticles. The Fe3O4 (at) MnO2 nano material prepared by the method has the characteristics of high detection speed, high sensitivity, low equipment dependence degree, simplicity in operation, low cost and the like. Compared with a commercial detection kit, the human rotavirus double-antibody sandwich detection method established by using the nano material has the advantages of higher detection sensitivity and lower detection limit.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nanomaterials, and specifically relates to an oxidase-like Fe3O4@MnO2 nanomaterial and a preparation method and application thereof. Background Art

[0002] Oxidase-like nanomaterials are a class of nanomaterials with natural oxidase activity, which can simulate the catalytic function of natural oxidases and catalyze the electron transfer process between molecular oxygen and substrate molecules. The materials include but are not limited to ferromagnetic nanoparticles, metal nanoparticles, cerium oxide nanoparticles, etc. According to the oxidized group of the substrate, oxidase-like nanomaterials can be classified into polyphenol oxidase-like, glucose oxidase-like, cytochrome C oxidase-like, etc.

[0003] Rotavirus is a double-stranded RNA virus belonging to the genus Rotavirus of the family Reoviridae. The virus has no envelope, only a capsid, and there are wheel-like protrusions on the outside of the capsid, similar to a wheel, so it is named rotavirus. The most common symptom of rotavirus infection is diarrhea. After infection, acute gastroenteritis is the most common complication; rotavirus can also cause damage to the respiratory system and central nervous system, and even cause shock in severe cases. Existing rotavirus detection methods mainly include electron microscopy, immunological detection, reverse transcription-polymerase chain reaction (RT-PCR), nucleic acid sequence determination and other methods; among them, electron microscopy detection equipment is expensive and has high operating requirements, and general hospitals do not have the conditions; immunological methods such as ELISA may have false positives and false negatives; RT-PCR requires professional laboratories and technicians, and the operation is relatively complicated; nucleic acid sequence determination requires high-precision sequencing instruments and data analysis technology. Therefore, inventing a method for rotavirus detection with higher sensitivity and easier operation has become a technical problem that needs to be solved at this stage. Summary of the invention

[0004] Based on the above technical problems to be solved by the present invention, the present invention adopts solvothermal method and potassium permanganate oxidation method to prepare Fe3O4@MnO2 nanomaterials with oxidase-like activity. The present invention uses the nanomaterials to establish a double-antibody sandwich detection method for human rotavirus. Compared with commercial detection kits, the detection sensitivity is higher and the detection limit is lower.

[0005] One of the purposes of the present invention is to provide an oxidase-like Fe3O4@MnO2 nanomaterial, wherein the oxidase-like Fe3O4@MnO2 nanomaterial comprises Fe3O4 nanoparticles and manganese dioxide; the manganese dioxide is generated in situ on the surface of the Fe3O4 nanoparticles.

[0006] Furthermore, the Fe3O4@MnO2 nanomaterial is tetrahedral in shape, with an average diameter of 25nm-60nm.

[0007] Furthermore, the method is applied to the preparation of the oxidase-like Fe3O4@MnO2 nanomaterial, and comprises:

[0008] S1, FeCl3·6H2O, ethylene glycol, and NaOH are stirred, sealed and heated, washed, and freeze-dried to obtain Fe3O4 nanoparticles;

[0009] S2, subjecting the Fe3O4 nanoparticles to ultrasonic treatment, stirring and washing with oleic acid to obtain a Fe3O4 / oleic acid complex;

[0010] S3, adding potassium permanganate solution to the Fe3O4 / oleic acid complex, and heating, washing,

[0011] The Fe3O4@MnO2 nanomaterial is obtained by freeze-drying.

[0012] Furthermore, the FeCl3·6H2O, ethylene glycol, and NaOH are stirred, sealed and heated, washed, and freeze-dried to obtain Fe3O4 nanoparticles, including:

[0013] S11, stirring FeCl3·6H2O, ethylene glycol, and NaOH to obtain a FeCl3·6H2O-ethylene glycol-NaOH mixed solution;

[0014] S12, transferring the FeCl3·6H2O-ethylene glycol-NaOH mixed solution into a polytetrafluoroethylene-lined stainless steel autoclave, and performing a heating treatment to obtain a black mixed product;

[0015] S13, washing the black mixed product with ultrapure water to obtain a washed black mixed product;

[0016] S14, subjecting the washed black mixed product to freeze-vacuum drying to obtain Fe3O4 nanoparticles.

[0017] Furthermore, the heating temperature is 180° C. to 200° C., and the heating time is 38 h to 45 h.

[0018] Furthermore, the Fe3O4 nanoparticles are ultrasonically treated, stirred and washed with oleic acid to obtain a Fe3O4 / oleic acid complex, comprising:

[0019] S21, ultrasonically dispersing the Fe3O4 nanoparticles into ultrapure water to obtain an ultrasonically dispersed Fe3O4 nanoparticle solution;

[0020] S22, adding oleic acid to the ultrasonically dispersed Fe3O4 nanoparticle solution, and performing heating and stirring treatment to obtain a black precipitate;

[0021] S23, using a magnet, ethanol and ultrapure water to separate and wash the black precipitate to obtain a Fe3O4 / oleic acid complex.

[0022] Furthermore, the heating and stirring is carried out at a temperature of 60° C. to 80° C. and for a time of 1 h to 3 h.

[0023] Furthermore, the Fe3O4 / oleic acid complex is added with a potassium permanganate solution, and subjected to heating, washing, and freeze-drying treatment to obtain the Fe3O4@MnO2 nanomaterial, comprising:

[0024] S31, adding a potassium permanganate solution to the Fe3O4 / oleic acid complex and performing a heating treatment to obtain a Fe3O4 / oleic acid complex reaction precipitate;

[0025] S32, using a magnet and deionized water to separate and wash the Fe3O4 / oleic acid complex reaction precipitate, respectively, to obtain a washed Fe3O4 / oleic acid complex reaction precipitate;

[0026] S33, freeze-drying the washed Fe3O4 / oleic acid complex reaction precipitate to obtain the Fe3O4@MnO2 nanomaterial.

[0027] Furthermore, the heating temperature is 40° C. to 60° C., and the heating time is 10 h to 14 h.

[0028] The second purpose of the present invention is to provide an application of an oxidase-like Fe3O4@MnO2 nanomaterial, including the application of the oxidase-like Fe3O4@MnO2 nanomaterial prepared by the preparation method in detecting human rotavirus.

[0029] Compared with the prior art, the present invention proposes an oxidase-like Fe3O4@MnO2 nanomaterial and its preparation method and application, which have the following beneficial effects:

[0030] 1. The detection system for detecting rotavirus based on the oxidase-like Fe3O4@MnO2 nanomaterial proposed in the present invention has a higher sensitivity, reaching 3.799 copies / μL.

[0031] 2. The present invention further optimizes the Fe3O4@MnO2-type oxidase-catalyzed reaction conditions, including the pH of the citric acid phosphate buffer solution, the amount of TMB, and the Fe3O4@MnO2-type oxide content. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.

[0033] Figure 1 A transmission electron microscope image (ad) and a size distribution histogram (e) of Fe3O4 nanoparticles according to an embodiment of the present invention are shown;

[0034] Figure 2 A transmission electron microscope image and mapping image of Fe3O4@MnO2 according to an embodiment of the present invention are shown;

[0035] Figure 3 A physical picture of Fe3O4 nanoparticles and Fe3O4@MnO2 nanoparticles according to an embodiment of the present invention is shown;

[0036] Figure 4 The electron diffraction XRD (a) and x-ray photoelectron spectroscopy XPS (b) diagrams of Fe3O4 nanoparticles before and after MnO2 encapsulation according to an embodiment of the present invention are shown;

[0037] Figure 5 The UV-visible absorption spectra of different reaction systems of the embodiments of the present invention (a) and the color development of the reaction system (b) are shown;

[0038] Figure 6 A graph showing the effect of pH on the activity of Fe3O4@MnO2-type oxidases according to an embodiment of the present invention is shown;

[0039] Figure 7 A diagram (a, b) showing the effect of TMB content on the color development of a reaction system and a diagram (c) showing the color development of the reaction system according to an embodiment of the present invention are shown;

[0040] Figure 8 The diagrams (a, b) of the activity of Fe3O4@MnO2-type oxidases with different contents and the diagram (c) of the color development of the reaction system according to the embodiment of the present invention are shown;

[0041] Fig. 9 A graph showing the absorbance change of a Fe3O4@MnO2-type oxidase catalyzed by different concentrations of TMB according to an embodiment of the present invention is shown;

[0042] Fig.10 Shown is a sensitivity diagram (a) of a double antibody sandwich detection system based on Fe3O4@MnO2 for detecting rotavirus and a color development diagram (b) of the reaction system according to an embodiment of the present invention;

[0043] Fig.11 A comparison chart of a double antibody sandwich detection system based on Fe3O4@MnO2 according to an embodiment of the present invention and a commercial ELISA kit is shown. DETAILED DESCRIPTION

[0044] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific embodiments in conjunction with the accompanying drawings.

[0045] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0046] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0047] The experimental materials and equipment involved in the present invention mainly include but are not limited to:

[0048] Reagents: FeCl3·6H2O (Tianjin Damao Chemical Reagent Factory, analytical grade); ethylene glycol (Sinopharm Chemical Reagent Co., Ltd., analytical grade); NaOH (Sinopharm Chemical Reagent Co., Ltd., analytical grade); potassium permanganate (Sinopharm Chemical Reagent Co., Ltd., analytical grade); ethanol (Sinopharm Chemical Reagent Co., Ltd., 95%);

[0049] Instruments: high temperature oven (Shanghai Boxun Medical Biological Instrument Co., Ltd., BGZ-146); ultrasonic disperser (Kunshan Ultrasonic Instrument Co., Ltd., KQ-500E); freeze dryer (Ningbo Xinzhi Biotechnology Co., Ltd., Sclentz-10N / A); multifunctional microplate reader (Molecular Devices, USA, SpectraMax M5); magnetic stirring water bath (Changzhou Jintan Liangyou Instrument Co., Ltd., SHJ-6A (brushless)).

[0050] The invention discloses an oxidase-like Fe3O4@MnO2 nanomaterial and a preparation method and application thereof, and its mechanism of action mainly includes: the Fe3O4@MnO2 nanomaterial has oxidase-like activity, can catalyze the TMB amino group to lose an electron and become a cationic free radical, so that TMB exists in the system in the form of a dimeric charge transfer complex, resulting in the reaction system being blue and having maximum absorption light intensity at 370nm and 652nm.

[0051] Example 1 :

[0052] The present invention provides a method for preparing Fe3O4 (Fe3O4@MnO2) nanoparticles wrapped with MnO2.

[0053] Hydrothermal synthesis of Fe3O4 nanoparticles: 5mmol FeCl3·6H2O was dissolved in 60mL ethylene glycol (EG). Subsequently, 1g of NaOH was added to the brown-yellow solution by magnetic stirring. The solution was then transferred to a 100mL polytetrafluoroethylene-lined stainless steel autoclave, sealed and kept at 200°C for 40 hours. The black product was washed with ultrapure water until the pH of the solution was neutral and then freeze-dried in a vacuum. The resulting black powder solid was sealed and stored at 4°C. Before each use, a certain mass of Fe3O4 nanoparticles was weighed and ultrasonically dispersed in ultrapure water.

[0054] Synthesis of Fe3O4 / oleic acid complex: Weigh 0.12g Fe3O4 nanoparticles and ultrasonically disperse them in 8mL ultrapure water. Then add 8mL 85% oleic acid to the above solution. Place the mixture in a nitrogen atmosphere and stir vigorously at 70°C for 1h. After the reaction, separate the black precipitate using a magnet, wash it three times with 95% ethanol, and then wash it with ultrapure water until the pH of the solution is neutral.

[0055] Synthesis of Fe3O4@MnO2 nanoparticles: Add 45mL of 2mM potassium permanganate solution to the above black precipitate, stir vigorously at 50℃ for 12h, separate the precipitate from the reaction medium with a magnet after the reaction, wash it with deionized water three times, and freeze-dry the product. Before each use, weigh a certain amount of Fe3O4@MnO2 nanoparticles and ultrasonically disperse them in ultrapure water.

[0056] result:

[0057] The Fe3O4@MnO2 nanoparticles prepared in Example 1 were observed by transmission electron microscopy. Figure 1 Fe3O4 nanoparticles transmission electron micrographs (ad) and size distribution histogram (e) are shown. Fe3O4 nanoparticles are tetrahedral in shape, with good dispersion and uniform size, and an average diameter of 40nm.

[0058] Figure 2 The surface morphology of Fe3O4@MnO2 nanoparticles. It can be seen that the electron microscope images of two different sizes of field of view and the mapping map of field of view e show that the surface of Fe3O4 is covered with a layer of irregular colloidal material, and the morphology has changed significantly. The mapping results show that the Mn element is evenly dispersed on the surface of Fe3O4 nanoparticles.

[0059] Compared with the Fe3O4@MnO2 nanoparticles prepared in Example 1, the Fe3O4@MnO2 nanoparticles have good dispersibility in water and are not easy to settle. Figure 3 shown.

[0060] Electron diffraction XRD results are shown in Figure 4 (a), indicating that the electron diffraction peaks of the two materials are consistent with the PDF standard card (#19-629), indicating that MnO2 encapsulation has no effect on the crystal structure of Fe3O4 nanoparticles. X-ray photoelectron spectroscopy XPS results are shown in Figure 4 (b) shows that the three main characteristic peaks come from Fe 2p, Mn 2p and O1s. The above characterization results all show that the present invention successfully prepared MnO2-encapsulated Fe3O4 nanoparticles.

[0061] The following Examples 2 and 3 present experiments to optimize enzyme-catalyzed reaction conditions.

[0062] Example 2 :

[0063] The present invention provides a Fe3O4@MnO2-type oxidase activity test.

[0064] In order to explore the enzyme-like activity of Fe3O4@MnO2, 20μL 500μM TMB solution was mixed with 25μL 10% H2O2 in a 96-well plate, and 10μL 0.5mg / mL Fe3O4@MnO2 suspension, 10μL 0.5mg / mL Fe3O4@MnO2 suspension + 25μL 10% H2O2, 10μL 0.5mg / mL Fe3O4 suspension and 10μL 0.5mg / mL Fe3O4 suspension + 25μL 10% H2O2 were added respectively, and finally an appropriate amount of pH 5.0 citrate phosphate buffer was added to make the total volume 200μL. The color change of the reaction system was observed, and the absorbance change of the reaction system was detected by UV-visible spectrophotometer.

[0065] Results: Figure 5 (a) and Figure 5 As shown in (b), Fe3O4 and Fe3O4@MnO2 can turn TMB into light blue in the presence of H2O2, while Fe3O4@MnO2 can directly catalyze TMB into blue in the absence of H2O2, and the color development is most obvious, with the strongest absorption peak at 650nm. The results show that Fe3O4@MnO2 has both oxidase activity and peroxidase activity, and the oxidase activity is stronger than the peroxidase activity.

[0066] Example 3 :

[0067] The present invention proposes an experiment for optimizing the catalytic reaction conditions of Fe3O4@MnO2-type oxidases.

[0068] (1) Optimization of pH of citrate phosphate buffer

[0069] To investigate the effect of pH on the oxidase activity of Fe3O4@MnO2, 80 μL of 500 μM TMB and 20 μL of 0.5 mg / mL Fe3O4@MnO2 were added to 100 μL of citrate phosphate buffer with pH values ​​of 3.0, 3.4, 3.8, 4.2, 4.6, 5.0, 5.4, 5.8, 6.2, 6.6, and 7.0, respectively.

[0070] Results: Figure 6 As shown, when the pH of the citrate phosphate buffer is 3.4, the absorbance of the reaction system is the strongest. As the pH of the citrate phosphate buffer increases, the absorbance of the reaction system decreases. The results show that when the pH of the citrate phosphate buffer is 3.4, Fe3O4@MnO2 has the best oxidase-like activity and can better catalyze the color development of the substrate TMB.

[0071] (2) Optimization of TMB dosage

[0072] To investigate the effect of TMB dosage on the activity of Fe3O4@MnO2-like oxides, 80 μL of gradient concentration (0 μM, 50 μM, 100 μM, 200 μM, 300 μM, 400 μM, 500 μM, 600 μM, 700 μM, 800 μM, 900 μM, 1000 μM) TMB solution was added to 20 μL 0.5 mg / mL Fe3O4@MnO2 and 100 μL pH 3.4 citrate phosphate buffer, respectively.

[0073] Results: Figure 7 (a, b) Effect of TMB content on the color development of the reaction system and the color development of the reaction system Figure 7 As shown in (c), the absorption light intensity of the reaction system at 650nm increases with the increase of TMB concentration, and reaches the maximum value when the TMB concentration is 800μM. Subsequently, the TMB concentration continues to increase, and the absorbance of the reaction system does not change significantly. The results show that 20μL 0.5mg / mLFe3O4@MnO2 can catalyze the color development of 800μM substrate TMB at most. When the content of substrate TMB in the reaction system is less than 800μM, TMB can be completely catalyzed for color development. When the TMB content exceeds 800μM, the excess TMB cannot be catalyzed, so the absorbance of the reaction system does not change significantly compared with the TMB concentration of 800μM.

[0074] (3) Fe3O4@MnO2 oxide content

[0075] To investigate the catalytic activity of Fe3O4@MnO2 with different contents, 20 μL of gradient concentration (0 μg / mL, 50 μg / mL, 100 μg / mL, 150 μg / mL, 200 μg / mL, 250 μg / mL, 300 μg / mL, 350 μg / mL, 400 μg / mL, 450 μg / mL and 500 μg / mL) of Fe3O4@MnO2 suspension was added to 80 μL 800 μM TMB and 100 μL pH 3.4 citrate phosphate buffer, respectively.

[0076] Results: Figure 8 (a, b) Activity diagram of Fe3O4@MnO2-like oxidases with different contents and color development of the reaction system Figure 8 As shown in (c), the Fe3O4@MnO2 content shows a good linear relationship with the absorption intensity at 650nm in the range of 0-450μg / mL. When the Fe3O4@MnO2 content exceeds 450μg / mL, the absorption intensity of the reaction system increases slowly. The results show that as the Fe3O4@MnO2 content increases, its ability to catalyze TMB color development also increases. When the Fe3O4@MnO2 content reaches 450μg / mL, the content of the substrate TMB that it can catalyze is also close to 800μM. Therefore, when the Fe3O4@MnO2 content is 500μg / mL, the absorption intensity of the reaction system does not increase significantly.

[0077] Example 4 :

[0078] The present invention proposes a Fe3O4@MnO2 enzyme kinetics research experiment.

[0079] In order to explore the catalytic kinetics of Fe3O4@MnO2-type oxidases on TMB, 80 μL of gradient concentrations (100 μM, 200 μM, 300 μM and 400 μM) of TMB solution were added to 30 μg / mL Fe3O4@MnO2 and 100 μL of pH 3.4 citrate phosphate buffer, and the changes in the absorbance intensity of the reaction system at 650 nm were detected.

[0080] Results: The initial velocity of the catalytic reaction was calculated according to the Beer-Lambert law, and the different concentrations of TMB and their initial velocity were fitted with double reciprocals. Finally, the Michaelis constant and the maximum reaction velocity were calculated according to the Michaelis-Menten equation.

[0081] A=Kbc (a)

[0082] Where K is the molar absorption coefficient, b is the thickness of the absorption layer, and c is the concentration of the absorbing substance.

[0083]

[0084] Where V0 is the initial reaction rate, V m represents the maximum reaction rate, [S] is the substrate concentration, K m is the Michaelis constant, which reflects the affinity of the enzyme for the substrate.

[0085] The results are as follows Fig. 9 As shown in the figure, 4s before the start of the catalytic reaction, the absorbance of the reaction solution showed a linear relationship with the reaction time. The linear fitting of the reaction in this period of time was performed, and the slope obtained was the initial velocity of the catalytic reaction of Fe3O4@MnO2 to different concentrations of TMB solution. Further, the TMB solution concentration was fitted with the corresponding initial velocity by a double reciprocal fitting, and V m =3.61×10 -4 M / min. The results show that the maximum rate of the oxidase-like Fe3O4@MnO2 catalytic reaction reaches 3.61×10 -4 M / min, which is conducive to faster catalysis of the substrate TMB color development.

[0086] Example 5 :

[0087] The invention provides an experiment for detecting rotavirus.

[0088] (1) Double antibody sandwich detection method for human rotavirus wa strain based on Fe3O4@MnO2 oxidase

[0089] ① Antibody coupling Fe3O4@MnO2: Add 12.5μL 25mg / mL NHS / EDC mixture to 1mL 0.5mg / mL Fe3O4@MnO2 suspension, mix and rotate at room temperature for 2h. Dilute rotavirus polyclonal antibody (purchased from Sigma, catalog number AB1129) 100 times, pipette 200μL into the activated Fe3O4@MnO2 suspension, mix and rotate at room temperature for 2h. Then use a magnet to collect the antibody-coupled magnetic beads, wash them 3 times with PBS, and finally suspend the antibody-magnetic bead complex in 1mL PBS containing 0.2% BSA.

[0090] ②Detection

[0091] Add 100 μL of 50 μg / mL monoclonal antibody (purchased from Abcam, catalog number ab181695) to each well of a 96-well plate and incubate overnight at 4°C. After washing with PBS three times, add 200 μL of 5% BSA for blocking and incubate at 37°C for 1 hour. Subsequently, wash with PBS-T three times. Add 100 μL of virus with different dilutions and incubate at 37°C for 3 hours. After washing with PBS-T three times, add 100 μL of antibody-coupled Fe3O4@MnO2 suspension and incubate at 37°C for 2 hours. After washing with PBS, add TMB colorimetric solution. Take pictures of the reaction system and detect the UV-visible absorption spectrum.

[0092] Results: Fig.10 (a) Sensitivity diagram of the dual antibody sandwich detection system based on Fe3O4@MnO2 for rotavirus detection Fig.10 (b) As shown in the color development diagram of the reaction system, the sensitivity of the double antibody sandwich detection system based on Fe3O4@MnO2 is 3.799 copies / μL. The results show that the double antibody sandwich detection system based on Fe3O4@MnO2 can detect rotavirus as low as 3.799 copies per microliter of sample, with high sensitivity, which is conducive to the accurate detection of human rotavirus.

[0093] (2) Comparison with commercial ELISA kits

[0094] The above gradient dilutions of human rotavirus were detected using a commercial human rotavirus ELISA detection kit.

[0095] Results: Fig.11 As shown, the double antibody sandwich detection system based on Fe3O4@MnO2 has higher sensitivity. The results show that the double antibody sandwich detection system based on Fe3O4@MnO2 has obvious advantages over commercial kits, with simple operation and lower detection limit, which is more conducive to the rapid and accurate detection of human rotavirus.

[0096] It should be noted that the term "comprises" or any other variation thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only these elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprises..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0097] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included within the scope of the claims of the present application.

Claims

1. An oxidase-like Fe3O4@MnO2 nanomaterial, characterized in that: The oxidase-like Fe3O4@MnO2 nanomaterial comprises Fe3O4 nanoparticles and manganese dioxide; the manganese dioxide is generated in situ on the surface of the Fe3O4 nanoparticles.

2. The oxidase-like Fe3O4@MnO2 nanomaterial according to claim 1, characterized in that: The Fe3O4@MnO2 nanomaterial is tetrahedral in shape and has an average diameter of 25nm-60nm.

3. A method for preparing an oxidase-like Fe3O4@MnO2 nanomaterial, characterized in that: Applied to the preparation of the oxidase-like Fe3O4@MnO2 nanomaterial according to claim 1, the method comprises: S1, FeCl3·6H2O, ethylene glycol, and NaOH are stirred, sealed and heated, washed, and freeze-dried to obtain Fe3O4 nanoparticles; S2, subjecting the Fe3O4 nanoparticles to ultrasonic treatment, stirring and washing with oleic acid to obtain a Fe3O4 / oleic acid complex; S3, adding potassium permanganate solution to the Fe3O4 / oleic acid complex, and performing heating, washing, and freeze-drying treatment to obtain the Fe3O4@MnO2 nanomaterial.

4. The method for preparing the oxidase-like Fe3O4@MnO2 nanomaterial according to claim 3, characterized in that: The FeCl3·6H2O, ethylene glycol and NaOH are stirred, sealed and heated, washed and freeze-dried to obtain Fe3O4 nanoparticles, including: S11, stirring FeCl3·6H2O, ethylene glycol, and NaOH to obtain a FeCl3·6H2O-ethylene glycol-NaOH mixed solution; S12, transferring the FeCl3·6H2O-ethylene glycol-NaOH mixed solution into a polytetrafluoroethylene-lined stainless steel autoclave, and performing a heating treatment to obtain a black mixed product; S13, washing the black mixed product with ultrapure water to obtain a washed black mixed product; S14, subjecting the washed black mixed product to freeze-vacuum drying to obtain Fe3O4 nanoparticles.

5. The method for preparing the oxidase-like Fe3O4@MnO2 nanomaterial according to claim 4, characterized in that: The heating temperature is 180° C. to 200° C., and the heating time is 38 h to 45 h.

6. The method for preparing the oxidase-like Fe3O4@MnO2 nanomaterial according to claim 3, characterized in that: The Fe3O4 nanoparticles are ultrasonically treated, stirred and washed with oleic acid to obtain a Fe3O4 / oleic acid complex, comprising: S21, ultrasonically dispersing the Fe3O4 nanoparticles into ultrapure water to obtain an ultrasonically dispersed Fe3O4 nanoparticle solution; S22, adding oleic acid to the ultrasonically dispersed Fe3O4 nanoparticle solution, and performing heating and stirring treatment to obtain a black precipitate; S23, using a magnet, ethanol and ultrapure water to separate and wash the black precipitate to obtain a Fe3O4 / oleic acid complex.

7. The method for preparing the oxidase-like Fe3O4@MnO2 nanomaterial according to claim 6, characterized in that: The heating and stirring is performed at a temperature of 60° C. to 80° C. and for a time of 1 h to 3 h.

8. The method for preparing the oxidase-like Fe3O4@MnO2 nanomaterial according to claim 3, characterized in that: The step of adding potassium permanganate solution to the Fe3O4 / oleic acid complex, and performing heating, washing, and freeze-drying to obtain the Fe3O4@MnO2 nanomaterial comprises: S31, adding a potassium permanganate solution to the Fe3O4 / oleic acid complex and performing a heating treatment to obtain a Fe3O4 / oleic acid complex reaction precipitate; S32, using a magnet and deionized water to separate and wash the Fe3O4 / oleic acid complex reaction precipitate, respectively, to obtain a washed Fe3O4 / oleic acid complex reaction precipitate; S33, freeze-drying the washed Fe3O4 / oleic acid complex reaction precipitate to obtain the Fe3O4@MnO2 nanomaterial.

9. The method for preparing the oxidase-like Fe3O4@MnO2 nanomaterial according to claim 8, characterized in that: The heating temperature is 40° C. to 60° C., and the heating time is 10 h to 14 h.

10. An application of an oxidase-like Fe3O4@MnO2 nanomaterial, characterized in that: Application of the oxidase-like Fe3O4@MnO2 nanomaterial as described in any one of claims 1 to 2, and the oxidase-like Fe3O4@MnO2 nanomaterial prepared by the preparation method as described in any one of claims 3 to 9 in detecting human rotavirus.

Citation Information

Cited By

  • Hollow Fe3O4-MnO2 flower-shaped nano-enzyme, preparation method and application of hollow Fe3O4-MnO2 flower-shaped nano-enzyme in vitamin C content detection

    CN122424830A